2018
DOI: 10.3390/catal8080318
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Copyrolysis of Cork Oak and Waste Plastic Films over HBeta

Abstract: The catalytic fast copyrolysis (CFCP) of cork oak (CoOak) and waste plastic films (WPFs) over HBeta(25) (SiO2/Al2O3: 25) was investigated using a thermogravimetric (TG) analyzer and a tandem micro reactor-gas chromatography/mass spectrometry (TMR-GC/MS) to determine the effectiveness of WPFs as the hydrogen donating cofeeding feedstock on the CFCP of biomass. By applying CFCP, the maximum decomposition temperatures of CoOak (373.4 °C) and WPFs (487.9 °C) were reduced to 364.5 °C for CoOak and 436.5 °C for WPFs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Nitrogen-containing heterocyclic compound (nicotine) is the main pyrolyzate of TL [9,28]. Limonene was produced by the decomposition of pectin, confirming previous reports [26,34]. Glycerol, a humectant in EHT, was also found in the pyrogram of TLs [9].…”
Section: Py-gc/ms Analysissupporting
confidence: 85%
“…Nitrogen-containing heterocyclic compound (nicotine) is the main pyrolyzate of TL [9,28]. Limonene was produced by the decomposition of pectin, confirming previous reports [26,34]. Glycerol, a humectant in EHT, was also found in the pyrogram of TLs [9].…”
Section: Py-gc/ms Analysissupporting
confidence: 85%
“…When the blending ratio of lignite, wheat straw, and plastic waste is 5:4:1, there exists a synergism effect for oil yield, and the oil yield and the gas yield are all the highest at this ratio. Park et al [87] reported the thermal decomposition temperature of cork oak and waste plastic films shifted to a lower temperature than their individual catalytic fast pyrolysis reactions due to the effective interaction between the pyrolysis intermediates, and the use of HBeta having strong acidity and appropriate pore size. Sergeyev et al [88] co-cracked PET with AR, observed an increase in the formation of light fraction.…”
Section: Co-pyrolysismentioning
confidence: 99%
“…Although they used the different HY having different acidity to that used in this study, they also found that HY produced the smaller amount of aromatics and larger amount of coke during the CFP of MP than HZSM-5. When the pore size of the catalyst was larger than the size required for the production of aromatics, the amount of coke could be increased because of the additional oligomerization of reaction intermediates inside the catalyst [26]. (…”
Section: Pyrolyzer-gas Chromatography/mass Spectrometry (Py-gc/ms) An...mentioning
confidence: 99%